Clean air for some: Unintended spillover effects of regional air pollution policies - Fang, Delin (Sci Adv, 2019)
China has enacted a number of ambitious pollution control policies to mitigate air pollution in urban areas. Unintended side effects of these policies to other environmental policy arenas and regions have largely been ignored. To bridge this gap, we use a multiregional input-output model in combination with an atmospheric chemical transport model to simulate clean air policy scenarios and evaluate their environmental impacts on primary PM(2.5) and secondary precursor emissions, as well as CO(2) emissions and water consumption, in the target region and spillover effects to other regions. Our results show that the reduction in primary PM(2.5) and secondary precursor emissions in the target regions comes at the cost of increasing emissions especially in neighboring provinces. Similarly, co-benefits of lower CO(2) emissions and reduced water consumption in the target region are achieved at the expense of higher impacts elsewhere, through outsourcing production to less developed regions in China.